An Assessment of The Challenges on Implementation of Affirmative Action in Ethiopian Secondary Schools - Tasgara, Asafa (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study was conducted an assessment on the implementation of affirmative action in case of Ethiopian secondary schools. The general objective of this research was to assess implementation of affirmative action in case of Ethiopian secondary schools.The data were collect from respondent the data was analyzed and summarized using both qualitative and quantitative method.. The findings from this study confirm that attitudes, perceptions practices and procedures related to affirmative action in Ethiopian secondary schools provide indicators of the challenges at implementation. In other words, this study has helped to identify the possible barriers for the implementation of affirmative action which could serve as a basis for further research. Having drawn up the above mentioned findings and remarks: Awareness-raising and sensitization plays a pivotal role in understanding the principle underlying affirmative action policies and practices. The implementation phase involves designing various strategies of implementation to have an effect on the goals identified in the planning phase.